Marker-assisted backcross breeding for heat tolerance in bread wheat (Triticum aestivum L.) - Bellundagi, Amasiddha; Ramya, K. T.; Krishna, Hari; Jain, Neelu; Shashikumara, P.; Singh, Pradeep Kumar; Singh, Gyanendra Pratap; Prabhu, Kumble Vinod (Frontiers in Genetics, 2022)
Manipulation of flowering time for adaptation through natural or genetic approaches may combat heat-stress damage that occurs at the reproductive stages in production conditions. HD2733, a popular wheat variety of the eastern plains of India, is largely sensitive to heat stress. Therefore, the current study aims to improve heat tolerance of HD2733 by introgression of QTLs associated with early anthesis and high kernel weight linked to markers Xbarc186 and Xgwm190, respectively, through marker-assisted backcross breeding (MABB) from a tolerant donor, WH730. A total of 124 simple sequence repeat (SSR) markers distributed evenly across the genome were used for the background selection. The alleles of Xbarc186 and Xgwm190 were fixed in BC2F1 and BC1F2 generations by selecting individual plants heterozygous for both marker loci and backcrossed with HD2733 and simultaneously selfed to generate BC2F1 and BC1F2 populations, respectively. Furthermore, the selected BC1F2 were selfed to generate the BC1F4 population. By background screening, a total of 39 BC2F3 and 21 BC1F4 families homozygous for the targeted QTLs with 90.9–97.9% and 86.8–88.3% RPG recoveries were selected. The best performing 17 BC2F3 and 10 BC1F4 lines were evaluated for various morpho-physiological traits. Phenotypic evaluation and multi-location trials of the introgressed lines under late sown conditions led to the selection of three promising lines with early anthesis and higher grain yield. The improved lines will serve as an excellent genetic material for functional genomics and expression studies to understand the molecular mechanisms and pathways underlying the stress tolerance.